QOLP-09. HEALTH ECONOMIC EVALUATION OF LOW-GRADE GLIOMA MANAGEMENT: A SYSTEMATIC REVIEW. (9th November 2020) - Hamidi, Nima; Fernandez, Ajay; Tuohy, Kyle; Mansouri, Alireza
Abstract: BACKGROUND: Diffuse low-grade gliomas (DLGGs, WHO Grade II gliomas) comprise 13-16% of all primary brain tumors. Although there has been a paradigmatic shift toward upfront maximal safe resection (MSR) for these heterogeneous tumors, it is important to consider the health economic perspective of this approach, compared with the traditional watch-and-wait approach, as well. OBJECTIVE: To conduct a systematic review of the health economic literature on the range of DLGG management options. METHODS: Following the PRISMA guidelines, Medline, EMBASE, The Central Registration Depository (CRD), EconPapers, and EconLit were searched for 'cost-effectiveness', 'health economics' and 'Low-grade glioma'. Grade I tumors were excluded. Pre-specified variables were extracted. All currencies were converted to USD. RESULTS: Among 258 abstracts, 28 were selected for full-text screening, and 3 were selected for this review. A European study evaluated the role of intraoperative electrical stimulation (IES). Although IES was associated with higher direct costs upfront (38, 662.70 vs 32, 116.10), this was offset by less long-term indirect costs (12, 222.30 vs 31, 927.10; p =0.023), greater QALY (4.8 vs 2.9; p =0.001), and an incremental cost-effectiveness ratio (ICER) of 1, 842.50. Another study evaluated the cost-effectiveness of adjuvant PCV+RT vs RT alone, finding greater QALY for the former (9.94 vs 5.17) and an ICER of 10, 186 per QALY gained. A third study evaluated the cost-effectiveness of adding 18 F-fluoroethyl-L-tyrosine (FET) PET to MRI, compared to preoperative MRI alone. This resulted in an ICER of 7, 193.58 for the baseline scenario (lowest reimbursement) and 10, 236.12 for the morbidity-adjusted reimbursement rate scenario (highest reimbursement). There were no studies evaluating the health economics of maximal upfront surgical resection to the watch-and-wait approach. CONCLUSION: We found a limited number of studies reporting on the health economics of DLGGs. Given the paradigmatic transition toward more aggressive upfront surgical resection, DLGG-specific health economic analyses are underway.